Colorectal cancer cells increase the production of short chain fatty acids by Propionibacterium freudenreichii impacting on cancer cells survival - Casanova, Marta Alexandra Rodrigues (2018)
Propionibacterium freudenreichii is a commercially relevant bacterium with probiotic potential. This bacterium can exert protective effects particularly against colorectal cancer (CRC), via the production of short chain fatty acids (SCFA), namely acetate and propionate. In this work, we aimed to evaluate the performance and adaptation capacity of P. freudenreichii to a simulated digestive stress using different culture media, namely YEL, Basal medium, Mimicking the Content of the Human Colon medium (MCHC) and DMEM. The effect of the fermented culture broth on CRC cells survival and of CRC cells conditioned media on the bacteria performance was also evaluated. Basal medium was found to be the best for P. freudenreichii to produce SCFA. MCHC medium, despite being the medium in which lower amounts of acetate and propionate were produced, showed higher acetate and propionate yields as compared to other media. We also observed that the presence of lactate in CRC cells conditioned growth medium resulting from cell metabolism, leads to an increased production of SCFA by the bacteria. The bacterial fermented broth successfully inhibited CRC cells proliferation and increased cell death. Our results showed for the first time that P. freudenreichii performance might be stimulated by extracellular lactate produced by CRC metabolic switch also known as Warburg effect, where cancer cells ferment glucose into lactate. Additionally, our results suggest that P. freudenreichii could be potentially used as a probiotic in CRC prevention at early stages of the carcinogenesis process and might help in CRC therapeutic approaches.